The Role of Acehnese Local Wisdom and Islamic Spirituality in Social Resilience Among Disaster Survivors - Khairunnisa, Dinda; Riva Nadia Putri; Hayatul Fitriya (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the roles of Acehnese local wisdom and Islamic spirituality in predicting social resilience among disaster-affected communities in Bireuen District, Aceh. Unlike previous models that treat cultural and religious factors as separate influences, this study proposes and tests an integrated framework in which local wisdom, Islamic spirituality, and social resilience are conceptualized as interconnected components. This approach offers a contextually grounded contribution to disaster resilience research in Muslim-majority communities. An explanatory quantitative design was employed, involving 250 respondents selected through proportionate stratified random sampling. Measurement instruments were adapted from the Social Capital Integrated Questionnaire (SC-IQ), the Muslim Religiosity Personality Inventory (MRPI), and the Conjoint Community Resiliency Assessment Measure (CCRAM). Data were analyzed using covariance-based Structural Equation Modeling (CB-SEM). The results indicate that local wisdom significantly and positively predicts social resilience (β = 0.417, p < .001), Islamic spirituality significantly predicts social resilience (β = 0.436, p < .001), and local wisdom significantly predicts Islamic spirituality (β = 0.528, p < .001). The model explains 58.2% of the variance in social resilience. These findings suggest that post-disaster recovery programs, particularly those implemented by local government agencies, non-governmental organizations, and disaster management institutions, may be more effective when they actively incorporate community deliberation practices, collective mutual aid traditions, and faith-based community engagement as core components of intervention strategies. Keywords: Aceh; Islamic spirituality; local wisdom; SEM; social resilience